2019
DOI: 10.1016/j.ymthe.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Micro-dystrophins with Enhanced Functionality

Abstract: Gene therapies using adeno-associated viral (AAV) vectors have advanced into clinical trials for several diseases, including Duchenne muscular dystrophy (DMD). A limitation of AAV is the carrying capacity ($5 kb) available for genes and regulatory cassettes (RCs). These size constraints are problematic for the 2.2-Mb dystrophin gene. We previously designed a variety of miniaturized micro-dystrophins (mDys) that displayed significant, albeit incomplete, function in striated muscles. To develop mDys proteins wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 63 publications
6
104
1
Order By: Relevance
“…It is quite likely that these large introns had relevant impact on the evolution of the human DMD gene leading to the acquisition of new functions. Recently, new DMD microgenes designed for gene therapy and inclusive of Hinge 1, Hinge 2 and nNOS domains resulted more functional in mice (Ramos et al, 2019). Based on this knowledge, it might be important to carefully define deletion intervals by annotating intronic breakpoints to better understand how a different genomic architecture or even locus rearrangements may impact on RNA transcription, protein translation machinery, and clinical outcome.…”
Section: Dmd Deletions and Duplications: Frequency Distribution Topmentioning
confidence: 99%
“…It is quite likely that these large introns had relevant impact on the evolution of the human DMD gene leading to the acquisition of new functions. Recently, new DMD microgenes designed for gene therapy and inclusive of Hinge 1, Hinge 2 and nNOS domains resulted more functional in mice (Ramos et al, 2019). Based on this knowledge, it might be important to carefully define deletion intervals by annotating intronic breakpoints to better understand how a different genomic architecture or even locus rearrangements may impact on RNA transcription, protein translation machinery, and clinical outcome.…”
Section: Dmd Deletions and Duplications: Frequency Distribution Topmentioning
confidence: 99%
“…This patient had a distant relative who also had the deletion with a mild phenotype and studies of the localization of his truncated minigene showed the truncated protein to be correctly localized at the sarcolemma [14]. Using transgenic mdx mice as a test model of function, several groups have designed further deletions to generate microdystrophins which also allow the integration of muscle specific promoters (for reviews see [15][16][17][18]). None of the reported microgenes will function as well as the full length dystrophin as they are by necessity a compromise, although encouraging data have been reported in the dog model of the disease [19].…”
Section: Gene Therapymentioning
confidence: 99%
“…This includes first the final product formulation to be delivered, with physical/physicochemical properties that may impact on each step of the delivery procedure. Considering the NA construct, its size impairs transfection efficiency, emphasizing the need for short and functional NA backbones and transgenes, such as mini‐ or micro‐dystrophin pDNA for DMD . The purity of pDNA batches is also a crucial parameter, especially regarding residual bacterial genomic DNA that can cause muscle damages .…”
Section: Other Miscellaneous Considerationsmentioning
confidence: 99%
“…For the latter application, the strong CMV promoter could be used because it confers a high expression level of the transgene in mammalian cells, whereas the duration of expression is probably not determinant . For long‐term expression applications, the use of a muscle specific promoter could be more adequate and ensure to restrict transgene expression to SM . However, it is important to note that, upon HLV, sustained expression could be obtained using various promoters (including the CMV promoter) .…”
Section: Other Miscellaneous Considerationsmentioning
confidence: 99%
See 1 more Smart Citation